Qualitative modelling of chemical processes - a weighted digraph (WDG) approach - Vianna, R (Computers & chemical engineering, 1995)
A qualitative reasoning methodology for describing complex chemical process is proposed. It focuses particularly on distributed parameters systems (DPS). This requires a considerable development beyond the techniques currently available for lumped parameters systems. The methodology extends the signed digraph approach due to Iri et al (1979) by incorporating functional weighting derived from estimates of relative sensitivity coefficients. Mass and energy accumulation terms from balance equations and temporal edges are used to capture the dynamic characteristics of the system. The methodology is illustrated by considering the qualitative simulation of two dynamic systems, a tank and a distillation column, when subject to disturbances in the feed flow rate. In general the procedure is able to provide a very satisfactory qualitative description of the dynamic trajectories of the systems and avoid ambiguous solutions. In particular it offers the prospect of being able to anticipate problems at the preliminary process design stage and points to ways of overcoming them.